(untitled) (CIPEEX, 2025)
Introduction: Flexibility is a crucial component of physical fitness, especially in the elderly, as it directly influences mobility and quality of life. This study aims to analyze the effects of a stretching program conducted three times a week for 12 weeks in a group of elderly individuals. Methods: A quasi-experimental study was conducted with 30 elderly individuals, aged between 65 and 80 years. Participants underwent 30-minute stretching sessions, three times a week, for 12 weeks. Flexibility was assessed using the sit and reach test before and after the intervention period. Results: The results showed a significant increase in the participants’ flexibility after the stretching program. The average reach in the sit and reach test increased from 20 cm to 28 cm, indicating an improvement in the range of motion of the lower limbs. Discussion: The findings suggest that regular stretching practice can significantly improve flexibility in the elderly, contributing to the maintenance of mobility and reduction of fall risk. These results are consistent with previous studies highlighting the benefits of stretching exercises in the elderly population. Conclusion: The 12-week stretching program, conducted three times a week, proved effective in improving flexibility in the elderly. It is recommended to include regular stretching in physical activity programs for this age group.